Question
upstudy study bank question image url

5. (4 pts) Use the limit definition of the derivative to find the derivative function of \( f(x)=x^{3}-5 x+1 \) note: \( (x+h)^{3}=x^{3}+3 x^{2} h+3 x h^{2}+h^{3} \)

Ask by Peterson Smith. in the United States
Feb 25,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

The derivative of \( f(x) = x^{3} - 5x + 1 \) is \( f '(x) = 3x^{2} - 5 \).

Solution

To find the derivative f '(x) of the function f(x) = x³ – 5x + 1 using the limit definition, start with:   f '(x) = limₕ→0 [f(x + h) – f(x)] / h Step 1. Write f(x + h):   f(x + h) = (x + h)³ – 5(x + h) + 1 Using the expansion provided, (x + h)³ = x³ + 3x²h + 3xh² + h³, we get:   f(x + h) = (x³ + 3x²h + 3xh² + h³) – 5x – 5h + 1 Step 2. Compute f(x + h) – f(x):   f(x + h) – f(x) = [x³ + 3x²h + 3xh² + h³ – 5x – 5h + 1] – [x³ – 5x + 1] Simplify by canceling like terms (x³, –5x, and +1):   f(x + h) – f(x) = 3x²h + 3xh² + h³ – 5h Step 3. Divide by h:   [f(x + h) – f(x)] / h = (3x²h + 3xh² + h³ – 5h) / h Factor an h from the numerator:   = h(3x² + 3xh + h² – 5) / h Cancel h (assuming h ≠ 0):   = 3x² + 3xh + h² – 5 Step 4. Take the limit as h approaches 0:   f '(x) = limₕ→0 (3x² + 3xh + h² – 5) Since h and h² go to 0 as h → 0:   f '(x) = 3x² – 5 Thus, the derivative function is:   f '(x) = 3x² – 5.

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

The Deep Dive

To find the derivative of the function \( f(x) = x^3 - 5x + 1 \) using the limit definition of the derivative, we start with the formula: \[ f'(x) = \lim_{h \to 0} \frac{f(x+h) - f(x)}{h} \] First, we calculate \( f(x+h) \): \[ f(x+h) = (x+h)^3 - 5(x+h) + 1 \] Substituting the binomial expansion \( (x+h)^3 = x^3 + 3x^2h + 3xh^2 + h^3 \): \[ f(x+h) = (x^3 + 3x^2h + 3xh^2 + h^3) - 5x - 5h + 1 \] Now, simplify \( f(x+h) \): \[ f(x+h) = x^3 + 3x^2h + 3xh^2 + h^3 - 5x - 5h + 1 \] Next, we compute \( f(x+h) - f(x) \): \[ f(x) = x^3 - 5x + 1 \] Thus, \[ f(x+h) - f(x) = (x^3 + 3x^2h + 3xh^2 + h^3 - 5x - 5h + 1) - (x^3 - 5x + 1) \] This simplifies to: \[ f(x+h) - f(x) = 3x^2h + 3xh^2 + h^3 - 5h \] Now, we substitute this into the limit definition: \[ f'(x) = \lim_{h \to 0} \frac{3x^2h + 3xh^2 + h^3 - 5h}{h} \] Factor out \( h \): \[ f'(x) = \lim_{h \to 0} \frac{h(3x^2 + 3xh + h^2 - 5)}{h} \] Canceling \( h \) from the numerator and denominator (assuming \( h \neq 0 \)), we get: \[ f'(x) = \lim_{h \to 0} (3x^2 + 3xh + h^2 - 5) \] Now as \( h \to 0 \): \[ f'(x) = 3x^2 - 5 \] Thus, the derivative function of \( f(x) = x^3 - 5x + 1 \) is: \[ f'(x) = 3x^2 - 5 \]

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy